Rethinking performance measurement models using a fuzzy logic system approach: a performative exploration on ownership in waste management. (February 2022) - Tafuro, Alessandra; Dammacco, Giuseppe; Esposito, Paolo; Mastroleo, Giovanni
Abstract: Literature on performance measurement in waste management service, usually considers assessment tools and methods that focus only on a specific dimension of performance and lacks methods and models that simultaneously consider more dimensions. In this study, adopting the fuzzy logic expert system, we propose a performance measurement model that simultaneously considers three performance dimensions: profitability, financial characteristics and efficiency. To show its empirical implementation, a quantitative analysis was developed regarding the service provided in the 106 Italian provincial capitals that have different owner structures (private, public and mixed). As output, the fuzzy logic system approach adopted generated a rating for the assessment of the performance of the entities, and then a ranking of the cities based on the same. The main results show that: 1) the public owned companies that provide the waste management service have an overall better performance than those with private or mixed ownerships; 2) cities that entrust the waste management service to the same company do not occupy an adjacent position in the ranking. As practical implications, the proposed model can help public administrators: a) to control the outcomes of their entities (as the TARI); b) to make a decision whether to provide solid waste management services directly or through a private entity chosen to provide the service in return for a negotiated fee; c) to compare waste management services provided in different cities in an objective way and to monitor their performance over time, with the aim of achieving continuous improvement. The model's outcomes are useful to assist public managers and politicians in assessing the compliance level of performance goals related to the solid waste service; while the overall performance index is a useful tool to assist the decision-making process leading to change either fully or partially, their nature from public to mixed or private. The proposed method is able to formalize and automate the decision-making process concerning the evaluation of the performance of waste management, reducing the distortions of the political and environmental context. Highlights: A performance measurement model for evaluate waste management service is proposed. The model has been applied to different service providers (public, mixed, private). Public owned companies have an overall better performance. The model can assist public manager and politicians in the decision making process.